LNG accident dynamic simulation: Application for hazardous consequence reduction - Sun, Biao; Guo, K. (Gas Technology Institute, 2013)
The definition of hazard area, centered inside the LNG stations, is essential for risk assessment in LNG industry. In this study, computational fluid dynamics (CFD) simulations have been conducted for the two main LNG hazards, LNG flammable vapor dispersion and LNG pool fire radiation, to determine the hazard exclusion area. The spatial and temporal distribution of hazard in complex spill scenario has been considered in CFD model. With the developed CFD code, the spray water curtains were studied as a shield to prevent LNG vapor dispersing. Two types of water spray curtain, flat curtain and cone, were analyzed to show their performance for reduction and minimization of the hazard influencing distance and area. The high expansion foam firefighting process was also studied with dynamic simulation of the foam action. The characteristics of the foam action on the reduction of LNG vaporization rate, vapor cloud and flame size as well as the thermal radiation hazard were analyzed and discussed.